Pinhão manso: crescimento e produtividade sob diferentes lâminas de irrigação e doses de nitrogêncio - Carvalho, Clayton Moura de (2012)
The state government of Ceara has sought, without much success, to revive the cotton crop, however, their high costs have prevented the plant expansion of cultivated area. One of the viable alternatives to occupy the space left by the cultivation of cotton is aimed at producing jatropha biodiesel. Given the above, this study aimed to evaluate the effects of different levels of irrigation water and nitrogen fertilizer on growth, production and nutritional status of jatropha. The study was conducted from September 2008 to February 2010, at the Experimental of the Bandeira Farm belonging to Br asil Ecodiesel agribusiness, located in Crateús - CE, located at 05 ̊23'25''S, 40 ̊57'38"W and 717 m altitude. The experimental design was randomized blocks in split plots. The treatments were composed from a combination of five water slides (50%, 75%, 100%, 125% and 150% of pan evaporation class "A") and four nitrogen levels (0%, 50% , 100% and 150% of nitrogen recommended), totaling 20 treatments with three replications. The analyzes of the growth occurred at 30, 60, 90, 120, 150, 180 and 210 days after pruning of uniformity. The variables analyzed were growth, production, efficiency of water use and plant nutritional status. The matric potential gradually decreased the extent of the blades there was an increase in the different treatments were irrigated and increasing the extent that the biomass of the plant increased. With greater water depth were achieved the highest growth and productivity. Nitrogen rates applied in this experiment were not sufficient to influence the treatment of growth and yield. There was a decline in the values of relative growth rate in height and stem diameter caused by climatic factors and the onset of flowering and fruit formation. The higher efficiency of water use in the production of fruits, seeds and albumen were found with the lower blade applied. The lower blade 735 mm was applied and every 2% increase of volume gave a mean increase of 1% in productivity variables. As semiarid cearense naturally present conditions scarcity becomes feasible cultivating Jatropha with the blade of 735 mm, since this provides a saving in water of 124% in relation to the greater applied blade. The order of accumulation of nutrients in the leaves, in general, was as follows: N> Ca > K > Mg > P.